Contamination of suture material and irrigation fluid over time during athroscopic reconstruction of the anterior cruciate ligament (primary and revision) and meniscus surgery. Issue 5 (28th May 2020) - Bartek, Benjamin; Garbe, Anja; Schelberger, Tarek Guy; Gwinner, Clemens; Perka, Carsten; Jung, Tobias
Aims and Objectives: During arthroscopic surgical procedures, some amount of irrigation fluid leaks from the surgical site and accumulates in the sterile reservoir. Whether these fluid collections show bacterial contamination over time in meniscus surgery and reconstruction of the anterior cruciate ligament (ACL) remains unclear. Materials and Methods: In this study, we include 200 patients. 100 patients undergoing ACL reconstruction and 100 patients undergoing meniscus surgery. We collected the samples of irrigation fluid before skin incision and every 15 minutes after the start of surgery. In addition, we evaluated the different types of suture material (Fast Fix and Outside-Inside threads in meniscus surgery and ACL reconstruction threads) for bacterial contamination. Results: At this point we evaluated samples of 152 patients (irrigation fluid of 152 patients, suture material of 100 patients). While no fluid sample showed contamination after 15 minutes, we overall detected bacterial contamination in 18, 4%. Suture material was contaminated with bacteria in 28% of cases. Conclusion: At this point, fluid surgical drape reservoirs were abacterial during the first 15 minutes but showed marked bacterial contamination over time. During surgery, irrigation fluid reservoirs should not be withdrawn by suction after skin incision. The tendency of bacterial contamination of the suture material and irrigation fluid reservoir over time has to be further explored. The continues flush and perioperative use of antibiotics might take an important impact on the low number of joint infection compared to the contamination ratio of the suture material. In addition, the effect of saturating suture material with antibiotics needs to be explored.